A flow cytometric approach to evaluate endothelial dysfunction in patients with type 2 diabetes mellitus - Chua, Yong Liang (2014)
Endothelial dysfunction is one of the common complications in type-2 diabetes mellitus (T2DM) known to increase the risk of cardiovascular diseases[1, 2]. Quantification of circulating endothelial cells (CECs), endothelial progenitor cells (EPC) and endothelial micro-particles (EMP) in peripheral blood is an essential indicator for the assessment of endothelial dysfunction and could serve as potential biomarkers for the risk assessment of vascular related diseases[3]. To achieve this, a rigorous method in flow cytometric analysis is important to ensure consistency and reliability of data. This study focused on the development of flow cytometric protocols for the quantification of CEC, EMP and EPC in type 2 diabetes mellitus patients and to determine correlations between variables of endothelial dysfunction to HbA1c and hyperglycemia. Treatment were given to patient to see any improvement for CEC, EMP and EPC population in endothelial dysfunction. Blood samples from 17 patients were analyzed at the interval of 4 months to allow treatment to take effect. The sample were analyzed phenotypically by flow cytometry for the expression of stem cell marker (CD34) and endothelial cell antigens (CD146, KDR/VEGFR-2), and enumeration of EPC, CEC and EMP. Three-color flow cytometric protocols used for the quantification of CECs and EMPs while the quantification of EPCs were based on the ISHAGE protocol. Correlation analysis was performed to find out if there was a relationship between endothelial function and blood sugar levels. From the experiment, HbA1c correlate to endothelial function as measured by the EPCs and CECs in this study. Quantification of CEC, EPC and EMP based on a negative control gating strategy was a more reliable and reproducible approach, and can be used to establish a clear relationship between endothelial dysfunction and common indicators in diabetes. The methods established in this study provide the potential use in enumeration of endothelial cells for monitoring T2DM patients.